Promise and challenges for discovering transcranial magnetic stimulation induced "numbsense"-Commentary on Ro & Koenig (2021) - Hurme Mikko; Railo Henry (Elsevier, 2025)
The notion that behavioral responses to stimuli can be mediated by separate unconscious and conscious sensory pathways remains popular, but also hotly debated. Recently, Ro and Koenig (2021) reported that when activity in somatosensory cortex was interfered with transcranial magnetic stimulation (TMS), participants could discriminate tactile stimuli they reported not consciously feeling. The study launches an interesting new area of research, helping to uncover mechanisms of unconscious perception that possibly generalize across different sensory modalities. However, we argue here that the study by Ro and Koenig also has several significant shortcomings, and it fails to provide evidence that pathways bypassing primary somatosensory cortex enable unconscious tactile discrimination. By referring to numerous studies investigating TMS-induced blindsight, we outline challenges in demonstrating unconscious sensory pathways using TMS. By facing to these challenges, research investigating TMS-induced numbsense has potential to stimulate progress in stubborn debates and reveal modality-general mechanisms of unconscious perception.